Air pollution exposure and pregnancy outcomes among women with polycystic ovary syndrome - Zhu, Qianqian; Cai, Jing; Guo, Haiyan; Zhao, Yan; Lin, Jiaying (Frontiers in Public Health, 2022)
Background Recently, the relationship between air pollution and reproductive outcomes has become a research focus. However, there is a lack of research on the relationship between air pollution and polycystic ovary syndrome (PCOS). Methods This is a retrospective cohort study included a total of 1,652 women with PCOS and 12,543 women without PCOS conducted from 1 January 2015 to 31 December 2019. The average daily concentration data of six air pollutants (PM2.5, PM10, O3, NO2, SO2, and CO) during different exposure windows were obtained. Generalized estimating equation models were used to evaluate the association of air pollution with pregnancy outcomes. Results Air pollutants were not found to have a significant association with pregnancy rates among patients with PCOS. However, each IQR increase in PM10 exposure during period 3 (embryo transfer to serum HCG test) was associated with the reduced clinical pregnancy rate (adjusted OR = 0.92, 95% CI: 0.84–0.99) for patients without PCOS. Patients without PCOS showed lower clinical pregnancy rates with increased exposure to NO2 during periods 2 (oocyte retrieval to embryo transfer) and 5 (start of gonadotropin medication to embryo transfer), with aORs and 95% CIs of 0.94 (0.88, 0.99) and 0.94 (0.88, 0.98), respectively. Each IQR increase in SO2 among patients without PCOS during periods 1 (start of gonadotropin medication to oocyte retrieval), 2, 5, and 6 (start of gonadotropin medication to serum HCG test) was related to a decrease in clinical pregnancy rate. For the live birth rate, no significant relationship was found between air pollutants, including PM2.5, PM10, SO2, NO2, CO, and O3, and the live birth rate for women with PCOS. However, women without PCOS presented a lower probability of live birth with exposure to SO2 during periods 1, 2, 5, and 6. Conclusion This retrospective study of reproductive-aged women observed no significant relationships between ambient pollutants and pregnancy outcomes among women with PCOS but found negative associations among women without PCOS.